Perancangan Sistem Pengelolaan Data Bantuan Masyarakat Miskin Berbasis Web - Uli Natalia Sinaga (ADA Research Center, 2025)
Managing data on aid for the poor using a computerized system properly and correctly can provide data information quickly and transparently. Unoptimized data management can cause various problems and slow down the performance of officers. This study aims to design and build a data management application for aid for the poor in Papande Village, North Tapanuli Regency. To date, population data and data on aid recipients at the Papande Village office in North Tapanuli Regency are still inputted manually. The data collection methods used were observation, interviews, and literature review. The research methods used were analysis, design, coding, testing, and implementation. The design of the data management system for aid for the poor is modeled using UML (Unified Modeling Language), which consists of usecase diagrams, class diagrams, sequence diagrams, and activity diagrams. These four diagrams are used to illustrate the flow of creating and using the data management application for aid for the poor, which will serve as a reference for programmers in developing the aid data management application. The design of this application is expected to facilitate officers in obtaining aid recipient information.